1990
DOI: 10.3109/00365529008997590
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine (5-Aminosalicylic Acid) Suppositories in the Treatment of Ulcerative Proctitis or Distal Proctosigmoiditis: A Randomized Controlled Trial

Abstract: A multicentre double-blind study was conducted to evaluate the efficacy and tolerability of 1 g or 1.5 g mesalazine daily compared with placebo in 94 patients with mild to moderate distal proctosigmoiditis (less than 20 cm). The study end point was the determination of clinical, endoscopic, and histologic remission rates at 4 weeks. Eleven patients, nine receiving placebo and two receiving 1.5 g mesalazine, withdrew during trial, mostly because of worsening of symptoms. At 4 weeks clinical remission was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 14 publications
0
56
0
5
Order By: Relevance
“…Mesalamine suppositories in a dose of 500 mg twice daily or 1,000 mg once daily are eff ective in the treatment of proctitis ( 103 ), and maintenance of remission ( 104 ), whereas mesalamine enemas in doses of 1 -4 g may be able to reach as proximal as the splenic fl exure and are eff ective in inducing ( 105,106 ) and maintaining ( 107 -109 ) remission in distal colitis. Topical corticosteroids, available in the United States as a 100 mg hydrocortisone enema, or as a 10 % hydrocortisone foam, are eff ective in acute therapy of distal colitis ( 110 -112 ) but have not proven eff ective in maintaining remission ( 77 ).…”
Section: Recommendations For Management Of Mild -Moderate Distal Colitismentioning
confidence: 99%
“…Mesalamine suppositories in a dose of 500 mg twice daily or 1,000 mg once daily are eff ective in the treatment of proctitis ( 103 ), and maintenance of remission ( 104 ), whereas mesalamine enemas in doses of 1 -4 g may be able to reach as proximal as the splenic fl exure and are eff ective in inducing ( 105,106 ) and maintaining ( 107 -109 ) remission in distal colitis. Topical corticosteroids, available in the United States as a 100 mg hydrocortisone enema, or as a 10 % hydrocortisone foam, are eff ective in acute therapy of distal colitis ( 110 -112 ) but have not proven eff ective in maintaining remission ( 77 ).…”
Section: Recommendations For Management Of Mild -Moderate Distal Colitismentioning
confidence: 99%
“…being the optimum dosage. 3,4,7,9 The preliminary results of the present open study suggest that the use of this new mesalazine microgranule 1 g suppository represents an ef®cient strategy for the topical treatment of ulcerative proctitis and distal proctosigmoiditis.…”
Section: Discussionmentioning
confidence: 99%
“…8 A dose-ranging trial demonstrated that mesalazine suppositories 500 mg b.d., represent the optimal dose in active proctitis. 9 Recently a new mesalazine 1 g suppository (Pentasa; Yamanouchi Pharma S.p.A., Milano, Italy) has been developed, from which the active ingredient, included in microgranules, is gradually released. This new suppository is small and has an oblong shape with a double apex, which facilitate its retention and retrograde spread.…”
Section: Introductionmentioning
confidence: 99%
“…As regards tolerability, none of the participating patients complained of adverse reactions attributable Intestinal segment of maximum spread and regional distribution of radioactivity (% dose) of the radiolabelled mesalazine enema at 4 h after dosing. For patients 1, 3, 5, 6, 9, 10, the disease extended to the rectum/sigmoid; for patients 2,4,7,8,11 to the distal descending colon and for patient 12 to the transverse colon.…”
Section: Resultsmentioning
confidence: 99%